Structure, morphology and photoluminescence emissions of ZnMoO4: RE 3+=Tb3+ - Tm3+ - X Eu3+ (x = 1, 1.5, 2, 2.5 and 3 mol%) particles obtained by the sonochemical method - Lovisa, L. X.; Oliveira, M. C.; Andrés, J.; Gracia, L.; Li, M. S.; Longo, E. [UNESP]; Tranquilin, R. L.; Paskocimas, C. A.; Bomio, M. R.D.; Motta, F. V. (Elsevier, 2018)
ZnMoO4 and ZnMoO4: RE3+ = 1% Tb3+, 1% Tm3+, x Eu3+ (x = 1, 1.5, 2, 2.5 and 3 mol%) particles were prepared by a sonochemical method. The influence of the dopant content on photoluminescent behavior was investigated. The X-ray diffraction results confirmed the formation of the α-ZnMoO4 phase with a triclinic crystalline structure. The influence of the chemical compositions on photoluminescence emissions has been studied and the results clearly show the specific emissions of Tb3+ and Eu3+, simultaneously, with a strong contribution of the matrix. Band gap values are in the range of 3.55–4.25 eV. From the values calculated for the CIE coordinates, it was observed that this material develops an emission tendency in the orange-red region. It has been demonstrated for the first time that the sample ZnMoO4: 1% Tb3+, 1% Tm3+, 2% molEu3+, presented higher photoluminescence intensity. At higher concentrations of RE3+, the quenching effect was observed. The morphology of samples are interpreted based on a comparative analysis of the calculated and experimental field emission scanning electron microscopy (FE-SEM) images. First-principle calculations at a density functional theory level were performed to obtain the values of surface energies and relative stability of the (120), (001), (011), (201), and (100) surfaces by employing the Wulff construction. A complete map of the available morphologies of ZnMoO4 and ZnMoO4:12.5%molEu3+ is obtained and a possible explanation for the transformation processes is provided in which the experimental and theoretical morphologies can match. The present study offers a fundamental knowledge that is expected to enable the fabrication of ZnMoO4-based phosphor materials with a controllable emission peak shift and intensity.
Keywords: Eu3+; Photoluminescence; Sonochemical method; Tm3+; ZnMoO4: Tb3+